Hubungan Faktor Ekonomi Terhadap Pemilihan Pengobatan pasien Fraktur - Eka Yuliani; Sri Maryuni; Mario Martini (Jurnal Ilmu Keperawatan Indonesia, 2020)
Fractures or often called fractures are the interruption of continuity of bone tissue and cartilage. Most fractures are caused by injury, trauma where there is excessive pressure on the bone. Fracture treatment consists of being a medical treatment and traditional medicine.The choice of traditional fracture treatment will have a hazard to the patient itself. One of the factors that influence the choice of fracture treatment is economic factors. Economic ability with the level of income and social household members determines how a person chooses and undergoes the desired treatment.The purpose of this study was to determine the Relations Between Economic Factors to the Selection of Treatment in Fracture Patients.Metodology in this study used a analytic correlation with a "cross sectional" approach. The population in this study were all patients treated with a medical diagnosis of fracture. The sample used in this study amounted to 46 respondents with a sampling technique used accidental sampling.From the analysis results obtained P Value 0.003, which means ≤ of the value α 0.05, it can be concluded that there is a relationship between economic factors on the choice of treatment in fracture patients. It is recommended for further researchers to examine more factors that influence treatment so that the most influential factors are seen on the selection of fracture treatment. Keywords : Fracture, Treatment, Economic Factors